(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
This review article analyzes three entries in the Dictionary of Political Ethics. Essays are devoted to the following topics: justice, good, and the person and the social unit. A brief discussion of the characteristics and their evaluation, as well as supplements, is provided. The supplements concern social justice, the common good, and relational conceptions of the person, including the ethics of protecting persons. Subsequent chapters with the same title as the aforementioned topics are devoted to these issues. The article is written from the perspective of classical philosophy. Attention is drawn to the origins of social justice and the concept of general justice, a distinction is made between the common good (of all humanity) and the good of individual communities, and attention is drawn to the modern contributions and contributions of modern philosophers to the development of a philosophy of the person as an alternative to traditional philosophical anthropology. The ethics of protecting persons not only assumes a personalist foundation for ethics but also formulates moral recommendations that protect and build interpersonal relationships, which are being replaced by economic relationships and mutual interest.